Analysis of Residual Chemicals on Filtering Facepiece Respirators After Decontamination - Salter, W.B. (J Occup Environ Hyg, 2010)
The N95 filtering facepiece respirator (FFR) is commonly used to protect individuals from infectious aerosols. Health care experts predict a shortage of N95 FFRs if a severe pandemic occurs, and an option that has been suggested for mitigating such an FFR shortage is to decontaminate and reuse the devices. Before the effectiveness of this strategy can be established, many parameters affecting respiratory protection must be measured: biocidal efficacy of the decontamination treatment, filtration performance, pressure drop, fit, and toxicity to the end user post treatment. This research effort measured the amount of residual chemicals created or deposited on six models of FFRs following treatment by each of 7 simple decontamination technologies. Measured amounts of decontaminants retained by the FFRs treated with chemical disinfectants were small enough that exposure to wearers will be below the permissible exposure limit (PEL). Toxic by-products were also evaluated, and two suspected toxins were detected after ethylene oxide treatment of FFR rubber straps. The results provide encouragement to efforts promoting the evolution of effective strategies for decontamination and reuse of FFRs.